The interaction of metallic ions onto activated carbon surface using computational chemistry software - AL Paredes-Doig; A Pinedo-Flores; J Aylas-Orejón; D Obregón-Valencia; MR Sun Kou (Adsorption Science & Technology)
Activated carbon was prepared from the seeds of aguaje palm ( Mauritia flexuosa L.f.) by a chemical activation with phosphoric acid. This activated carbon was used for adsorbing metal ions: Pb(II), Cd(II), and Cr(III). To understand the mechanism of adsorption of these heavy metals (Cr, Cd, and Pb), the activated carbon surface was oxidized with nitric acid (1 M) increasing the oxygenated surface groups showing an increasing in their adsorption capacities of these metals. The oxidized activated carbon slightly increased the maximum adsorption capacity to 5–7%. The order of adsorption for unoxidized and oxidized activated carbons was Pb> Cd> Cr. This experimental information was corroborated by molecular modeling program Hyperchem 8 based adsorption mainly on two factors: the electron density and orbitals—highest occupied molecular orbital and lowest unoccupied molecular orbital.Activated carbons were characterized by adsorption/desorption of N 2 , obtaining an increase of microporous surface area for oxidized activated carbon. An increase of surface acidity and a reduction of isoelectric points were observed in oxidized activated carbon. According to these results, the adsorption of metal ions is favored in contact with an oxidized activated carbon, which has more amount of phenolic and carboxylic functional groups. Similarly, decreasing the isoelectric point indicates that the surface has a higher negative charge. The surface information was corroborated by Hyperchem, which indicates that the surface of the oxidized activated carbon has a higher electron density, indicating a larger amount of electrons on its surface, which means the surface of oxidized activated carbon charges negatively and thereby attracts metal ions.